Cardiovascular Effects of Metformin - B. T. Kurmanbekova; A. M. Noruizbaeva (Рациональная фармакотерапия в кардиологии, 2022)
Type 2 diabetes mellitus is one of the most important independent risk factors for the development, progression and mortality from cardiovascular diseases (CVD). The world communities are faced with the question of developing the optimal management tactics for such comorbidity patients. Thus, the prescribed drug should not only have an adequate hypoglycemic effect, but also have a number of cardioprotective properties, be safe in patients with CVD, and possibly even improve the prognosis and reduce mortality rates. This review is devoted to a representative of the biguanide class - metformin, which is one of the earliest and most effective antihyperglycemic drugs, both as monotherapy and in combination with other antihyperglycemic drugs and insulin; while the evidence base for its cardiovascular profile is only gaining momentum. Thus, the purpose of this review is to highlight the cardiovascular effects of metformin in the context of recent research.